Cardiometabolic risk factors of post-bariatric patients two years after COVID-19 pandemic onset: a longitudinal study - Raysa Manuelle Santos Rocha; Márcia Ferreira Cândido de Souza; Danielle Villela Costa; Larissa Monteiro Costa Pereira; Jamille Oliveira Costa; Rosely de Jesus Nascimento; Andreia Ferreira de Aragão Rabelo; Alex Menezes dos Santos-Junior; Mario Francisco Dantas de Santana-Filho; André Luiz de Jesus Morais; Leonardo Baumworcel; José Rodrigo Santos Silva; et al. (Scientific Reports)
Abstract The COVID-19 pandemic’s prolonged extension may have had a long-term negative impact on weight and metabolic parameters associated with the effectiveness of bariatric surgery. The aim of this study was to assess the impact of the COVID-19 pandemic on cardiometabolic risk markers and weight outcomes of post-bariatric patients. This is a longitudinal study carried out with patients who underwent bariatric surgery before the COVID-19 pandemic. Anthropometric, lipid, glycemic profile, blood pressure, eating behavior and physical activity parameters obtained through face-to-face consultations from 2019 to 2022 were evaluated. An increase in BMI (p = 0.001), percentage of weight gain (p < 0.001), postoperative weight regain rate (p = 0.002), fasting blood glucose (p < 0.001), and glycosylated hemoglobin (p < 0.001) was identified. There were reductions in the percentages of excess weight loss (p = 0.001) and physically active individuals (p = 0.016). These changes were only triggered after the pandemic years. Uncontrolled eating, emotional eating, and physical inactivity were identified as risk factors for weight gain during the pandemic. Prepandemic weight regain rate was risk factor for increased fasting blood glucose. Two years after the pandemic onset, the study participants exhibited increased rates of weight regain, reduced excess weight loss, and an increase in fasting blood glucose and glycosylated hemoglobin parameters.